کلام اقبال اردو میں قرآنی تلمیحات: ایک تحقیقی جائزہ: Qur’anic Allusions in Urdu Poetry of Iqbal: A Research Analysis - Muhammad Dawood Jamal; Hafiz Muhammad Faizan Ul Hassan; Dr Majid Rashid (Al Manhal Research Journal, 2025)
Allama Muhammad Iqbal was a proficient poet, veteran thinker and skilled philosopher. Besides this, he was a pro Islamist. He studied Greek philosophy and the modern philosophy. He studied the holy Quran very deeply, and he used his very specific version of Quranic Symbolism. He referred to Quranic verses very frequently and effortlessly in his poetry. He studied Islamic philosophers as well such as Rumi, Razi, and Ghazali. He announced Rumi as his spiritual mentor and his ideal philosopher. He studied and wrote about Friedrich Nietzsche, Wolfgang von Goethe, Arthur Schopenhauer and Henri Bergson. He discussed the most important issues of philosophy such as the genesis of time and space, free will, ego and religion. But he was deeply affected by the Holy Quran. In his last days he expelled all his book collection from his room, except the Quran. This explains his love of the Quran. Sometimes he refers to a Quranic verse so briefly and symbolically that readers feel it very hard to understand his intentions and misinterpret him. So, there always has been a need for authentic helpers for Iqbal lovers. Among these helpful writings are highly specified articles with very narrow and deep focus on single dimensions of interpretation. In the following lines I tried to explain those verses of Iqbal which refer to Quranic verses.